Lost in Translation: The Effects of Incentive Compensation on Strategy Surrogation - Choi, Jongwoon (Willie); Hecht, Gary W.; Tayler, William B. (The Accounting Review, 2012)
ABSTRACT To facilitate managers' decision-making, firms develop strategic performance measurement systems that translate strategy into performance measures. Ideally, managers see measures for what they are—imperfect proxies for intangible strategic constructs. However, managers may fail to fully appreciate the fact that measures are merely representations of the strategic constructs, and act as though the measures are the construct of interest—a phenomenon we label surrogation. In this paper, we investigate whether and how the use of strategically linked performance measures for compensation purposes affects managers' propensity to exhibit surrogation. In accordance with the attribute substitution framework (Kahneman and Frederick 2002), we predict incentive compensation exacerbates surrogation, and that this effect is more prevalent when managers are compensated on a single measure of a strategic construct than when managers are compensated on multiple measures of a strategic construct. Via two experiments, we find support for these hypotheses. Our paper contributes to the literature on strategic performance measurement systems by highlighting the tendency of managers to use measures as surrogates for strategy. More generally, we identify a by-product of contracting on imperfect performance measures not previously considered in extant literature, and establish when consideration of costs of this by-product are likely to be critical.